STRATEGI OMNICHANNEL SEBAGAI UPAYA PENINGKATAN TRUST DAN BRAND IMAGE PADA MASA PANDEMI COVID-19 KOTA SURABAYA - Aldea Mita Cheryta; Rudiatno Rudiatno (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2022)
ABSTRACTThis study analyzes omnichannel strategies as an increase in trust and brand image using qualitative methods with indepth interview data analysis. The focus of this research is omnichannel, trust, and brand image which seeks to be analyzed so that it can explain social phenomena that occur in society. The location of this study was conducted in the city of Surabaya, the location of the study was determined because the complex problems discussed in this study were experienced by consumers and producers in the city of Surabaya. Although it is not fully researched by each region, considering the urgency of this research is in the online marketplace where all consumers and producers in the city of Surabaya can be actively involved in market mechanisms. The study broadens the understanding of the field of omnichannel retail in a number of dimensions, firstly the research assumes a linear consumer decision-making process. Second, the literature and structure review brings the spotlight needed to observe omnichannel based on a broader management perspective. This focus is more context-specific and fragmented from the findings about the decision-making process. Fourth, this study shows results in online business people who do not understand much about omnichannel strategies carried out by the segmentation of medium to upper business people.